Nilai-nilai Pendidikan Islam dalam Ibadah Zakat: Mengungkap Pesan Al-Qur’an dan Hadis - Ahmad Zumaro; Nurul Afifah; Umar, Umar (Tarbawiyah Jurnal Ilmiah Pendidikan, 2025)
This study aims to uncover the Islamic educational values embedded in zakat based on the messages of the Qur'an and Hadith, as well as its relevance to shaping individual and societal character. Zakat, as one of the pillars of Islam, encompasses dimensions beyond ritual worship. The main values explored include social justice, solidarity, responsibility, and spiritual purification. Social justice in zakat embodies equitable wealth distribution to reduce social disparities. Solidarity fosters empathy and care for others, strengthening social cohesion. Responsibility and trust educate individuals to act with integrity in fulfilling moral and social obligations. Spiritual purification instills sincerity, curbs materialism, and aligns individuals with higher spiritual values. This study concludes that the Islamic educational values in zakat are relevant to shaping individuals with strong moral and spiritual character while fostering a harmonious and just society. These findings highlight the urgency of zakat as a character education instrument in addressing global challenges such as social inequality and individualism and reinforcing zakat's role as a pillar of rahmatan lil 'alamin.